Facile fabrication of self-reporting micellar and vesicular structures based on an etching-ion exchange strategy of photonic composite spheres of poly(ionic liquid). Issue 3 (13th January 2021) - Gao, Ning; Zhou, Kang; Feng, Kai; Zhang, Wanlin; Cui, Jiecheng; Wang, Peng; Tian, Li; Jenkinson-Finch, Mary; Li, Guangtao
Abstract : Micellar and vesicular photonic compartments capable of reporting the chemical environment as well as introducing user-defined functionalities were successfully constructed. Abstract : Micellar and vesicular structures capable of sensing and reporting the chemical environment as well as facilely introducing user-defined functions make a vital contribution to constructing versatile compartmentalized systems. Herein, by combining poly(ionic liquid)-based photonic spheres and an etching-ion exchange strategy we fabricate micellar and vesicular photonic compartments that can not only mimic the structure and function of conventional micelles and vesicles, but also sense and report the chemical environment as well as introducing user-defined functions. Photonic composite spheres composed of a SiO2 template and poly(ionic liquid) are employed to selectively etch outer-shell SiO2 followed by ion exchange and removal of the residual SiO2 to afford micellar photonic compartments (MPCs). The MPCs can selectively absorb solvents from the oil/water mixtures together with sensing and reporting the adsorbed solvents by the self-reporting optical signal associated with the uniform porous structure of photonic spheres. Vesicular photonic compartments (VPCs) are fabricated via selective infiltration and polymerization of ionic liquids followed by etching of the SiO2 template. Subsequent ion exchange introduces desirable functions to the VPCs. Furthermore, we demonstrate that the thickness and the anisotropic functions of VPCs can be facilely modulated. Overall, we anticipate that the micellar and vesicular photonic compartments with self-reporting optical signals and user-defined functions could serve as novel platforms towards multifunctional compartmentalized systems.